MALAYSIAN STUDENTS’ ACHIEVEMENT IN TIMSS 2011: DOES SCIENCE INQUIRY REALLY MATTER? (Malaysian Journal of Learning and Instruction, 2017)
Purpose â€“ This study investigates the relationship of student and teacher level variables on Trend for International Mathematics and Science Study (TIMSS) 2011 Science achievement among Malaysian students. Specifically, it aims to examine the effect of studentsâ€™ achievement when a science inquiry approach is considered. Method â€“ Thirteen educational context variables were selected from the teacher and student questionnaires and were tested on the TIMSS 2011Science achievement. The data were retrieved from the IEA official website and consisted of 177 Science teachers and 5,549 Grade Eight students. A secondary data analysis was employed to examine the relationships between the variables from the perspective of the Dynamic Model of Educational Effectiveness Research. A two-level model of the Hierarchical Linear Modelling (HLM) consisting of Teacher-Student Level was employed. The 13 independent variables are: student gender, parentsâ€™ education level, home educational resources, liking Science, valuing Science, teacher gender, class size, teacher who emphasises on academic success, inquiry approach, science assessment, frequency of science test, teacher experience and teacher qualification. The nested data of students and teachers were analysed using Hierarchical Linear Modelling 6.0 statistical software.Findings â€“ The study finds that teacher differences between schools account for 70% variation in the studentsâ€™ achievement due to factors, such as teacher gender, enthusiasm of teacher in emphasising the academic success of students and class size. However, Science Inquiry is not a contributor to studentsâ€™ achievement in Science; it has only a moderating effect on studentsâ€™ achievement to value Science learning. Significance â€“ The findings have important implications for stakeholders, specifically to Teachersâ€™ Training Institutions, Curriculum Development Centres and the Teachersâ€™ Development Division, on the Science teachersâ€™ quality in Malaysia. Affective domain of the students is equally important as the cognitive domain and should not be ignored.